Mathematical model of an excitation by electron beam of “whispering gallery” modes in cylindrical dielectric resonator - Galaydych, K.V.; Lonin, Yu.F.; Ponomarev, A.G.; Prokopenko, Yu.V.; Sotnikov, G.V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
For generation of oscillations of millimeter and submillimeter wave lengths can be used "whispering gallery" modes excited in a dielectric resonator by an azimuthally-modulated electron beam. The mathematical model of excitation of these modes is constructed. The dispersion equation for determination of eigen frequencies of "whispering gallery" modes is obtained, eigen waves and their norms are found. Using them, the integro-differential equations for eigen wave amplitudes are derived. Построена математическая модель возбуждения мод «шепчущей галереи». Получено дисперсионное уравнение, определяющее собственные частоты этих мод, найдены собственные волны и их нормы. Используя их, получено интегро-дифференциальное уравнение для амплитуд возбуждаемых волн. Побудована математична модель збудження мод «шепочучої галереї». Отримано дисперсійне рівняння, що визначає власні частоти цих мод, знайдені власні хвилі і їх норми. Використовуючи їх, отримане интегро-диференційне рівняння для амплітуд збуджуваних хвиль.